World Poverty, Animal Minds and the Ethics of Veterinary Expenditure. (1st August 2009) - Hadley, John; O'Sullivan, Siobhan
In this paper we make an argument for limiting veterinary expenditure on companion animals. The argument combines two principles: the obligation to give and the self-consciousness requirement. In line with the former, we ought to give money to organisations helping to alleviate preventable suffering and death in developing countries; the latter states that it is only intrinsically wrong to painlessly kill an individual that is self-conscious. Combined, the two principles inform an argument along the following lines: rather than spending inordinate amounts of money on veterinary care when a companion animal is sick or injured, it is better to give the money to an aid organisation and painlessly kill the animal.